Comparative study of oral mucosa micronuclei in smokers and alcoholic smokers - Oliveira, Lidiana Ubiña [UNESP]; Lima, Celina Faig [UNESP]; Salgado, Miguel Ângelo Castillo [UNESP]; Balducci, Ivan [UNESP]; Almeida, Janete Dias [UNESP] (My University, 2012)
Objective: To compare the frequency of micronuclei and metanucleated anomalies in the oral mucosa of smokers, alcoholic smokers, and nonsmokers. Study Design: Three groups were studied: group I, 15 smokers; group II, 16 alcoholic smokers; and group III, 20 nonsmokers. Three smears from the lateral left border of the tongue were processed for Feulgen staining. A minimum of 300 cells per participant were examined for the quantification of micronuclei and metanucleated anomalies. Results: The Kruskal-Wallis test showed no significant difference in the frequency of micronuclei (p = 0.602) or karyorrhexis (p = 0.114) among the three groups, but there was a significant difference in the frequency of broken eggs, binucleated cells, and karyolysis (p=0.001). Spearman's correlation indicated an influence of the number of cigarettes per day on micronuclei frequency. Tobacco caused significant alterations in the exfoliative cytology (broken eggs, binucleated cells, and karyolysis) of chronic smokers, but not in the frequency of micronuclei or karyorrhexis, despite the observation of a larger absolute number of micronuclei in group II. Conclusion: The action of genotoxic agents (tobacco and alcohol) causes alterations in the frequency of micronuclei and metanucleated anomalies. © Science Printers and Publishers, Inc.
Keywords: Alcohol; Micronuclei; Oral mucosa; Tobacco